An exploration of the embedding of ritual behavior in advertising texts - Grad, Iulia (Journal for the study of religions and ideologies, 2023)
This article analyzes, drawing on conceptual tools from communication philosophy and cultural anthropology, the integration of ritual behavior into advertising texts. The first part of the paper presents a general approach to the presence of ritual behaviors in promotional communication. Next, a conceptual framework is outlined, enabling a nuanced exploration of the presence of ritual in advertising texts. For this purpose, the concept of liminality, as addressed by Victor Turner, and Culinau's analysis of the concept of subjective power and its link to rites, with their integrative and compensatory functions, are primarily utilized. Subsequently, three frequently employed archetypal figures in branding, characterized by a shared trait of reticence towards social norms, are presented. The final part of the paper focuses on how the incorporation of ritualized behaviors contributes to shaping the advertising message. These behaviors, by presenting a ritual sequence easily repeated by the audience, become effective tools in conveying the significant message of the advertisement and associating the brand with profound meanings.